Data for paper 'Homogenised model for the electrical current distribution within a submerged arc furnace for silicon production' - Luckins, E K; Oliver, J M; Please, C P; Sloman, B M; Van Gorder, R A (University of Oxford, 2021)
The attached files contain the data for the paper 'Homogenised model for the electrical current distribution within a submerged arc furnace for silicon production' by Ellen Luckins, James Oliver, Colin Please, Benjamin Sloman, and Robert Van Gorder, published in the European Journal of Applied Mathematics, 2021 (doi: 10.1017/S0956792521000243). See the READ ME file for a description of the data.